The Introduction and Application of Sports Analytics in Professional Sport Organizations - Michael Mondello; Christopher Kamke (Journal of Applied Sports Management, 2014)
While professional sports organizations continue to seek techniques to augment their on-field success, the growth of sports analytics has concurrently become increasingly competitive and complex. However, despite these recent developments and availability of data, much of the information shared between organizations, academicians, and practitioners is often limited and anecdotal. In this paper, we sought to provide a brief overview of analytics and subsequently share several best practice examples of how one National Hockey League (NHL) franchise, the Tampa Bay Lightning, integrates analytical techniques into several core business entities. An organizational emphasis on Customer Relationship Management (CRM) provides management with valuable data about their customers’ current purchasing habits and potentially may predict future purchases. In addition, analytical techniques have assisted the organization in developing and implementing both dynamic and variable ticket pricing strategies to procure additional revenues. We conclude the paper with suggestions for future research and applications. Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:8.0pt; mso-para-margin-left:0in; line-height:107%; mso-pagination:widow-orphan; font-size:12.0pt; mso-bidi-font-size:11.0pt; font-family:"Times New Roman","serif"; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: sports analytics; technology; innovation